Low-melt-index poly (butylene oxalate) as well as efficient preparation method and application thereof
By using the intrinsic catalysts titanium oxalate and micro-crosslinker, the melt index of polybutylene oxalate was solved, and the problem of excessive flow rate and poor thermal stability of polybutylene oxalate at high temperature was solved, and biodegradation was achieved Material matching and wider processing windows, and improve mechanical properties and degradation capabilities.
Patent Information
- Application Number
- CN202411500301.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The melting index of existing polybutylene oxalate is too high, resulting in the flow rate at high temperatures that cannot meet the needs of industrial processing, and has poor thermal stability, which is prone to thermal degradation, affecting storage stability and mechanical properties.
The intrinsic catalyst titanium oxalate and microcrosslinker significantly reduce the melt index of polybutylene oxalate in transesterification and polycondensation reaction, improve the transesterification reaction activity through hydrogen bond coordination, and use polycondensation catalyst to improve thermal stability .
The melt index of polybutylene oxalate is significantly reduced, making it matched with biodegradable materials such as PBAT or PBS, broadening the processing window, improving molecular weight, mechanical properties and degradation capabilities, and enhancing storage stability.
Smart Images

Figure CN119192547A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material synthesis, and particularly relates to polybutylene oxalate with a low melting index, high mechanical strength and high hydrolysis rate, which is easy to process, and an efficient preparation method and application thereof. Background Art
[0002] Adhering to the principle of polymer materials from CO 2 Produces and eventually generates CO 2 Based on the principle of 2 New polymer monomers from sources. Among them, electrocatalytic reduction of CO 2 The synthesis of oxalic acid and the preparation of the intermediate dimethyl oxalate by the coal-to-ethylene glycol process provide a new way to produce low-cost oxalic acid-based polymer monomers. As a linear aliphatic oxalate, although poly(ethylene glycol oxalate) has mechanical properties that meet market demand, it has a low crystallinity and a fast degradation rate, which poses a risk of unexpected degradation during the shelf life. The introduction of long-chain diols alleviates the unexpected degradation of poly(hexanediol oxalate) and poly(octanediol oxalate), but they have problems such as low strength and poor mechanical properties. Therefore, the structure of poly(butylene oxalate) that combines mechanical properties with degradation ability has attracted widespread attention.
[0003] Patent CN102219891A discloses a method for preparing polybutylene oxalate, wherein the ratio of diethyl oxalate to butanediol is 1:1 to 1:3, oxalic acid is preferably used as a catalyst, and N 2 The reaction was carried out at 80-170°C for 0.5-5h, and then at 110-180°C and a vacuum of 200-500Pa for 3-8h to obtain polybutylene oxalate with an intrinsic viscosity of only 0.05-0.45dL / g. The low intrinsic viscosity makes it unable to meet the material application requirements.
[0004] Patent CN115677988A relates to an in-situ preparation method of polybutylene oxalate. Under the co-catalytic action of a titanium-sulfonic acid composite catalyst and a second type of metal oxide, polybutylene oxalate is obtained through three steps of ester exchange, pre-polycondensation and final polycondensation. The obtained target product has a characteristic viscosity of 1.4-1.8 dL / g and a weight-average molecular weight of 130-180 kDa. However, the invention requires precise control of the molar ratio of the raw materials to 1:1, which can easily cause a significant decrease in the product molecular weight and performance deviation due to an imbalance in the feed ratio.
[0005] During the melt polycondensation process, dimethyl oxalate or diethyl oxalate has poor thermal stability and is easily degraded by heat, which leads to thermal degradation in the later stage of polycondensation, reduced molecular weight, increased content of terminal carboxyl and free carboxyl groups, and increased acid value and hydroxyl value of the product, which not only reduces storage stability but also reduces its mechanical properties. In addition, PBS itself has a high melt index. In industry, chain extension or solid phase polycondensation is required to further reduce the melt index of PBS polymer pellets to meet the processing requirements of PBS. Similar to PBS, due to the relatively low melting point (107°C) and the characteristics of the full fat chain segment, the melt index of the high molecular weight polybutylene oxalate obtained by conventional polymerization is too high, reaching more than 5 times that of PBAT with similar molecular weight, resulting in the melt flowing too fast at high temperature, which does not match the melt index of materials such as PBAT or PBS currently used on a large scale, and the processing window is narrow and demanding.
[0006] Therefore, finding new catalysts to make oxalic acid-based polyesters more thermally stable, prevent thermal degradation during melt polycondensation, and significantly reduce their melt index to meet industrial needs has become a key challenge in synthesizing high-quality poly(butylene oxalate). Summary of the invention
[0007] The main purpose of the present invention is to provide a novel intrinsic catalyst for preparing polybutylene oxalate, as well as low melt index polybutylene oxalate and an efficient preparation method thereof, so as to overcome the deficiencies in the prior art.
[0008] Another object of the present invention is to provide the application of the low melt index polybutylene oxalate.
[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides an efficient preparation method of low melt index polybutylene oxalate, which comprises: Oxalate and 1,4-butanediol are used as raw materials, a micro-crosslinking agent is added, and low melt index polybutylene oxalate is obtained through ester exchange reaction and polycondensation reaction under the action of intrinsic catalyst titanium oxalate and polycondensation catalyst.
[0010] In some embodiments, the intrinsic catalyst titanium oxalate is prepared by the following steps: at room temperature under nitrogen protection, using metallic titanium as the anode, placing it in an electrolyte containing oxalic acid and passing a constant current of 20-50 mA for more than 60 minutes to obtain the intrinsic catalyst titanium oxalate.
[0011] The present invention also provides a low melt index polybutylene oxalate prepared by the above preparation method, the structural formula of which is shown in formula (1): ; Among them, R 1At least one structural unit selected from polyol compounds, x, y, and n are all integers, x=1-20, y=1-3, and n=20-100.
[0012] In some embodiments, the polyol compound includes at least any one of glycerol, pentaerythritol, 1,2,6-hexanetriol, trimethylolpropane, and trimethylolethane.
[0013] The embodiment of the present invention also provides the use of the aforementioned low melt index polybutylene oxalate in the fields of agricultural mulch films, artificial seed coatings, drug sustained-release carriers, human implant components or transient electronic devices.
[0014] Compared with the prior art, the beneficial effects of the present invention include: 1) In the efficient preparation method of low melt index polybutylene oxalate provided by the present invention, the intrinsic catalyst titanium oxalate is used to undergo hydrogen bond coordination with oxalate ester, which can significantly improve the transesterification reaction activity of the oxalate ester bond, thereby greatly improving the production and removal rate of by-product methanol or ethanol in the transesterification process, and significantly improving the esterification efficiency; at the same time, the addition of a micro-crosslinking agent significantly reduces the melt index of polybutylene oxalate, so that it can match the currently large-scale applied biodegradable materials such as PBAT or PBS, providing new materials for truly realizing all-natural domain degradable materials, solving the problem that the melt flows too fast at high temperature and does not match the fluidity of large-scale applied biodegradable materials such as PBAT or PBS, and broadening the processing window.
[0015] 2) The low melt index polybutylene oxalate prepared by the present invention has higher molecular weight and mechanical properties, good crystallization ability, biocompatibility and degradation ability, and has broad application prospects in agricultural mulch films, artificial seed coatings, drug sustained-release carriers, human implant components and transient electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 is the infrared FTIR spectrum of the intrinsic catalyst titanium oxalate prepared by electrocatalysis in Example 1 of the present invention; Figure 2 The NMR of polybutylene oxalate prepared using titanium oxalate in Example 2 of the present invention is 1 H-NMR spectrum; Figure 3 is a DSC graph of polybutylene oxalate prepared using titanium oxalate in Example 2 of the present invention; Figure 4 is a stress-strain diagram of polybutylene oxalate prepared using titanium oxalate in Example 2 of the present invention; Figure 5 This is a graph showing the hydrolysis mass loss of polybutylene oxalate prepared using titanium oxalate in Example 2 of the present invention. DETAILED DESCRIPTION
[0018] In view of the problems existing in the above-mentioned prior art, after long-term research and a large number of experiments, the inventors of this case proposed an efficient preparation method for low melt index polybutylene oxalate, and synthesized an intrinsic catalyst titanium oxalate by an electrocatalytic method. Under the action of a small amount of micro-cross-linking agent, the polybutylene oxalate has a high molecular weight, a low acid value and a hydroxyl value, and has excellent mechanical properties and degradation properties. The melt index at 190°C is 5g / 10min-20g / 10min, which matches the current market bio-based plastic raw materials such as PBAT and PBS. The dosage of polybutylene oxalate can be adjusted to meet the requirements of different application scenarios for the stability and degradation rate of degradable materials.
[0019] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.
[0021] As one aspect of the technical solution of the present invention, it involves a new type of intrinsic catalyst for preparing polybutylene oxalate, that is, the use of titanium oxalate as a catalyst in the preparation of polybutylene oxalate.
[0022] As another aspect of the technical solution of the present invention, an efficient preparation method of low melt index polybutylene oxalate involves: using oxalate and 1,4-butanediol as raw materials, adding a micro-crosslinking agent, and obtaining low melt index polybutylene oxalate through ester exchange reaction and condensation reaction under the action of intrinsic catalyst titanium oxalate and condensation polymerization catalyst.
[0023] In some embodiments, the efficient preparation method of low melt index polybutylene oxalate comprises: Under a protective atmosphere, a first mixed reaction system comprising oxalate, 1,4-butanediol, a micro-crosslinking agent and an intrinsic catalyst titanium oxalate is subjected to an ester exchange reaction to obtain a micro-crosslinked polyester oligomer; Under vacuum conditions, a second mixed reaction system comprising the micro-crosslinked polyester oligomer, a polycondensation catalyst, an antioxidant and a heat stabilizer is subjected to a polycondensation reaction to prepare low melt index polybutylene oxalate.
[0024] The main inventive concept of the present invention is: using oxalic acid esters such as dimethyl oxalate or diethyl oxalate and 1,4-butanediol as raw materials, adding a micro-crosslinking agent, and obtaining polybutylene oxalate through transesterification reaction and polycondensation reaction under the action of an intrinsic catalyst titanium oxalate and a polycondensation catalyst. The present invention selects the intrinsic catalyst titanium oxalate to undergo hydrogen bond coordination with the oxalic acid ester, which can significantly improve the transesterification reaction activity of the oxalic acid ester bond, thereby greatly improving the generation and removal rate of byproduct methanol or ethanol during the transesterification process, and significantly improving the esterification efficiency.
[0025] In some embodiments, the oxalate ester may be one or more of dimethyl oxalate, diethyl oxalate, etc., but is not limited thereto.
[0026] In some embodiments, the intrinsic catalyst titanium oxalate and the micro-crosslinking agent are added to the reaction system before the transesterification reaction.
[0027] In some preferred embodiments, the intrinsic catalyst titanium oxalate is prepared by the following steps: at room temperature under nitrogen protection, using metallic titanium as an anode, placing it in an electrolyte containing oxalic acid and passing a constant current of 20-50 mA for more than 60 minutes to obtain the intrinsic catalyst titanium oxalate.
[0028] In some more specific preferred embodiments, the intrinsic catalyst titanium oxalate suitable for polybutylene oxalate is prepared by the following steps: S1: Under nitrogen protection and room temperature, titanium metal is used as the anode, placed in oxalic acid electrolyte and a constant current is passed for more than 60 minutes, and a light yellow solid is precipitated in the electrolyte; S2: Under nitrogen protection and room temperature, filter the light yellow solid and then use ethanol to filter 3 to 5 times to elute the oxalic acid in the solid. After evaporation and crystallization, yellow prismatic crystals are obtained, which is the intrinsic catalyst titanium oxalate.
[0029] Specifically, the chemical reaction formula of the intrinsic catalyst is as follows: ; In some embodiments, when feeding, the molar ratio of the oxalate to 1,4-butanediol is 1:1.2 to 1:1.5.
[0030] In some embodiments, the micro-crosslinking agent includes a polyol compound, preferably any one or more combinations of propylene glycol, pentaerythritol, 1,2,6-hexanetriol, trimethylolpropane, trimethylolethane, etc., but not limited thereto. The addition of the micro-crosslinking agent in the present invention significantly reduces the melt index of polybutylene oxalate, so that it can match the currently large-scale biodegradable materials such as PBAT or PBS, providing new materials for truly realizing all-natural domain degradable materials, solving the problem that the melt flows too fast at high temperature and does not match the fluidity of large-scale biodegradable materials such as PBAT or PBS, and broadening the processing window.
[0031] In some embodiments, the amount of the micro-crosslinking agent is 1% to 3% of the molar fraction of the oxalate (such as dimethyl oxalate or diethyl oxalate).
[0032] In some embodiments, the molar ratio of the micro-crosslinking agent to 1,4-butanediol is 1:40 to 1:150.
[0033] In some embodiments, the amount of titanium oxalate used as an intrinsic catalyst accounts for 0.2‰ to 1.5‰ of the mass fraction of oxalate (such as dimethyl oxalate or diethyl oxalate).
[0034] In some embodiments, the temperature of the transesterification reaction is 130° C. to 150° C., and the time of the transesterification reaction is 120 min to 180 min.
[0035] In some embodiments, the efficient preparation method includes: before the transesterification reaction, adding the intrinsic catalyst titanium oxalate and the micro-crosslinking agent into the reaction system.
[0036] In some more preferred embodiments, the efficient preparation method includes: before the transesterification reaction, placing oxalate (such as dimethyl oxalate or diethyl oxalate), 1,4-butanediol, intrinsic catalyst titanium oxalate, and micro-crosslinking agent together in a reaction chamber (such as a reactor), heating to 130°C to 150°C within 30 minutes and continuously stirring mechanically to carry out the transesterification reaction. The zero point is when a drop of small molecule methanol or ethanol is collected, and the end point of the transesterification reaction is when the mass of methanol or ethanol collected is more than 95% of the theoretical value. The time of the transesterification reaction is 120min to 180min.
[0037] In some embodiments, the condensation catalyst is a metal organic compound. The present invention uses a combination of metal organic compounds such as antimony catalysts, titanium catalysts, tin catalysts, and germanium catalysts as a condensation agent, which significantly improves the thermal stability of polybutylene oxalate, reduces the content of free carboxyl and hydroxyl groups, improves stability, avoids the degradation of polybutylene oxalate in the melt condensation reaction, and has a higher molecular weight and mechanical properties, good crystallization ability, biocompatibility and degradation ability.
[0038] Furthermore, the antimony-based catalyst may be any one or more combinations of antimony trioxide, antimony acetate, ethylene glycol antimony, triethyl antimonate, etc., but is not limited thereto.
[0039] Furthermore, the titanium-based catalyst may be any one or more combinations of titanium isopropoxide, tetrabutyl titanate, and tetraethyl titanate, but is not limited thereto.
[0040] Furthermore, the tin-based catalyst may be any one or more combinations of stannous chloride, stannous oxalate, dibutyltin oxide, stannous octoate, and stannous trifluoromethanesulfonate, but is not limited thereto.
[0041] Furthermore, the germanium-based catalyst may be any one or more combinations of germanium dioxide, germanium chloride, methyl triethylgermanate, tetraethylgermanate, and tetrabutylgermanate, but is not limited thereto.
[0042] In some embodiments, the amount of the polycondensation catalyst used accounts for 0.5‰ to 2‰ of the mass fraction of the oxalate (such as dimethyl oxalate or diethyl oxalate).
[0043] In some embodiments, the amount of the antioxidant used accounts for 1‰ to 2‰ of the molar mass of the oxalate (such as dimethyl oxalate or diethyl oxalate).
[0044] In some preferred embodiments, the antioxidant is selected from phenolic antioxidants, wherein the phenolic antioxidant may include at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,6-di-tert-butyl-4-methylphenol, 2,2-methylenebis(4-methyl-6-tert-butylphenol), etc., but is not limited thereto.
[0045] In some embodiments, the thermal stabilizer is selected from phosphorus-based stabilizers, wherein the phosphorus-based stabilizer may include at least one of phosphorous acid, diphenyl phosphate, triphenyl phosphate, triphenyl phosphite, etc., but is not limited thereto.
[0046] In some embodiments, the amount of the heat stabilizer used accounts for 1‰ to 5‰ of the molar mass of the oxalate (such as dimethyl oxalate or diethyl oxalate).
[0047] In some embodiments, the efficient preparation method includes: adding a polycondensation catalyst, an antioxidant, and a thermal stabilizer before the polycondensation reaction.
[0048] In some preferred embodiments, the temperature of the condensation reaction is 190°C~210°C, the pressure in the early stage of the condensation reaction is 200~1000Pa, and the time in the early stage of the condensation reaction is 60min~90min; the pressure in the middle stage of the condensation reaction is 50~200Pa, and the time in the middle stage of the condensation reaction is 30min~60min; the pressure in the late stage of the condensation reaction is below 10Pa, and the time in the late stage of the condensation reaction is 60min~90min.
[0049] As one aspect of the technical solution of the present invention, it involves low melt index polybutylene oxalate prepared by the above-mentioned efficient preparation method.
[0050] Furthermore, the structural formula of the low melt index polybutylene oxalate is shown in formula (1): ; Among them, R 1 At least one structural unit selected from polyol compounds, x, y, and n are all integers, x=1-20, y=1-3, and n=20-100.
[0051] In some embodiments, the polyol compound includes at least any one of glycerol, pentaerythritol, 1,2,6-hexanetriol, trimethylolpropane, trimethylolethane, and the like.
[0052] In some embodiments, the low melt index polybutylene oxalate has an intrinsic viscosity of 1.4 dL / g~1.7 dL / g, a weight average molecular weight of 120000 g / mol~180000 g / mol, an acid value of 15 mol / t~25 mol / t, a hydroxyl value of 30KOHmg~40KOHmg / g, a melt index of 5g / 10min~20g / 10min at 190°C, and an initial thermal decomposition temperature of 310°C~340°C.
[0053] In some embodiments, the glass transition temperature of the low melt index polybutylene oxalate is -23°C to 21°C, the melting point is 104°C to 106°C, the elastic modulus is 500 to 550 MPa, the tensile strength is 50 MPa to 60 MPa, and the elongation at break is 300% to 500%; the water contact angle of the polybutylene oxalate film prepared by hot pressing is 30° to 40°, CO 2 The transmittance is 1barrer~3barrer,2 The permeability is 2.5barrer~4barrer; the mass loss after 35 days of hydrolysis is 80%~95%, and the remaining mass after 35 days of seawater degradation is 40%~60%.
[0054] As one aspect of the technical solution of the present invention, it involves the application of the aforementioned low melt index polybutylene oxalate.
[0055] Furthermore, the low melt index polybutylene oxalate has good crystallization ability and mechanical properties as well as a controllable degradation rate, and has broad application prospects in the fields of agricultural mulch films, artificial seed coatings, drug sustained-release carriers, human implant components, and transient electronic devices.
[0056] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.
[0058] Hereinafter, the low melt index polybutylene oxalate will be further described through the following specific examples.
[0059] In the embodiment, the nuclear magnetic resonance spectroscopy ( 1 H-NMR was measured on a Bruker 400 AVANCE III Spectrometer at a frequency of 400 MHz and trifluoroacetic acid (TFA) as the solvent.
[0060] In the examples, gel permeation chromatography (GPC) (Agilent PL-GPC220) was performed at 40°C using chromatography grade chloroform as the eluent at a flow rate of 1.0 mL min -1 Select polystyrene standard to calibrate molecular weight.
[0061] In the embodiment, the melt index is measured by an electric melt flow rate meter of model YK-3651A according to the test standard ASTM D 1238, and the mass of the melt flowing within 10 minutes at 190° C. and 2.16 kg pressure is measured, and the unit is g / 10 min.
[0062] In the embodiment, the acid value is measured by volumetric titration. The sample is dissolved in a phenol-chloroform mixed solvent (volume ratio 2:3) by reflux, cooled, and then titrated with a potassium hydroxide-ethanol standard titration solution (c(KOH)=0.05 mol / L) using a 0.1% mass fraction bromophenol blue ethanol solution as an indicator. The content of the terminal carboxyl group is calculated based on the volume consumed by the standard titration solution.
[0063] In the embodiment, the hydroxyl value is measured by volumetric titration. The sample is dissolved in the acetylated mixed solution by reflux, and phenolphthalein is used as an indicator while hot. 1 mol / L sodium hydroxide standard solution is used for titration. The hydroxyl content is calculated based on the volume consumed by the standard titration solution.
[0064] In the examples, thermal analysis was performed using differential scanning calorimetry (Mettler Toledo DSC) at a heating rate of 10 °C / min under N 2 The temperature range is -50℃ to 150℃.
[0065] In the embodiment, the mechanical property test was conducted using an Instron 5567 universal material testing machine, with the sample strip dimensions of 35.0 mm in length, 2.0 mm in width, and 1.0 mm in thickness, and the tensile speed was 20 mm / min.
[0066] In the examples, the water contact angle (CA) is measured at room temperature and normal pressure using a WCA analyzer OCA20 (Dataphysics Ltd., Germany).
[0067] In the embodiment, Labthink VAC-V2 was used for 2 and CO 2 The barrier properties of O 2 and CO 2 The measurement was carried out under the conditions of 23°C and 50%RH. The sample size was Φ = 97mm and the penetration area was 38.5cm 2 .
[0068] In the embodiment, a phosphate buffer solution is used as a degradation solvent, and a hydrolysis degradation test is carried out in a 37° C. constant temperature water oscillator, wherein the sample is 10 mm in length, 10 mm in width, and 0.5 mm in thickness.
[0069] In the embodiment, 35 g of sea salt is used to calibrate in a 1 L volumetric flask, and a seawater degradation test is performed at 8-18° C., wherein the sample is 10 mm in length, 10 mm in width, and 0.5 mm in thickness.
[0070] Example 1 (Preparation of intrinsic catalyst titanium oxalate) Under nitrogen protection at 25°C, titanium metal was used as the anode, and a 0.5 mol / L oxalic acid ethanol solution was placed. The redox potential was set to 1.00 V, and a constant current of 20 mA was passed for 60 min. A light yellow solid was precipitated in the ethanol solution. The light yellow solid was filtered and then ethanol was used to filter 5 times to elute the oxalic acid in the solid. The temperature was raised to 15°C above the boiling point of ethanol, and the excess ethanol was evaporated and then naturally cooled to room temperature 25°C to obtain yellow prismatic crystals, which are the intrinsic catalyst titanium oxalate. The FTIR structure is as follows: Figure 1 .
[0071] Comparative Example 1 3 ml of TiCl with a molar ratio of 1:2 4 The hydrochloric acid solution was added dropwise to a 5% w / v oxalic acid aqueous solution and stirred for 60 minutes. The reaction solution was gradually added dropwise to an excess of cold saturated ethanol solution and stirred for 30 minutes. The solution was allowed to stand for 5 hours to allow it to fully settle. The solution was washed with ethanol by suction for 3-5 times and dried in a vacuum oven at 50°C for 5 hours to obtain a solid powder, which was titanium oxalate.
[0072] Example 2 (Preparation of polybutylene oxalate) Dimethyl oxalate and 1,4-butanediol were added into the reactor in molar amounts of 0.30 mol and 0.36 mol, and then the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 0.3‰ of the total molar mass of all acid raw materials) and the micro-crosslinking agent pentaerythritol (accounting for 1% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 140°C within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 2 hours to obtain a micro-crosslinked polyester oligomer.
[0073] Under nitrogen protection and continuous stirring, add polycondensation catalyst tetrabutyl germanate (accounting for 1.2‰ of the total molar mass of all acid raw materials), stabilizer triphenyl phosphite (accounting for 1.5‰ of the total molar mass of all acid raw materials) and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol (accounting for 2‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 195°C, gradually reduce the vacuum degree to 200Pa, react for 90min; continue to reduce the vacuum degree to 50Pa, react for 60min; continue to reduce the vacuum degree to below 10Pa, react for 60min. Discharge the material under nitrogen protection to obtain the target polybutylene oxalate.
[0074] The NMR of the polybutylene oxalate prepared in this example 1 H-NMR Figure 2 As shown, it can be seen that the structure of the obtained polybutylene oxalate is clear; the DSC curve of the polybutylene oxalate is as follows Figure 3As shown in FIG. 1 , the glass transition temperature of polybutylene oxalate is -23.2°C and the melting point is 104.4°C; the stress-strain curve of polybutylene oxalate is shown in FIG. Figure 4 As shown, the elastic modulus is 528MPa, the tensile strength is 53.4MPa, and the elongation at break is 325%.
[0075] The test results show that the polybutylene oxalate prepared in this embodiment has an intrinsic viscosity of 1.43 dL / g, a weight average molecular weight of 123000 g / mol, an acid value of 24 mol / t, a hydroxyl value of 38 KOHmg / g, a melt index of 11 g / 10 min, an initial thermal decomposition temperature of 332°C, a water contact angle of 32°, and a CO 2 The transmittance is 1.63 barrer, O 2 The permeability is 3.12 barrer, and the mass loss in phosphate buffer after 35 days of degradation is 90%, and the mass loss in seawater after 35 days of degradation is 48%. Figure 5 shown.
[0076] Comparative Example 2 Dimethyl oxalate and 1,4-butanediol were added into the reactor in molar amounts of 0.30 mol and 0.36 mol, and then a micro-crosslinking agent, pentaerythritol (accounting for 1% of the total molar mass of all acid raw materials) was added. Under nitrogen protection, the temperature was raised to 140° C. within 30 minutes for esterification. The mechanical stirring speed was 140 r. After reacting for 3 hours, a polyester oligomer was obtained.
[0077] Under nitrogen protection and continuous stirring, add polycondensation catalyst tetrabutyl germanate (accounting for 1.2‰ of the total molar mass of all acid raw materials), stabilizer triphenyl phosphite (accounting for 1.5‰ of the total molar mass of all acid raw materials) and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol (accounting for 0.5‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 195°C, gradually reduce the vacuum degree to 200Pa, react for 90min; continue to reduce the vacuum degree to 50Pa, react for 60min; continue to reduce the vacuum degree to below 10Pa, react for 60min. Discharge the material under nitrogen protection to obtain the target polybutylene oxalate.
[0078] The polybutylene oxalate prepared in this comparative example has an intrinsic viscosity of 0.83 dL / g, a weight average molecular weight of 86000 g / mol, an acid value of 30 mol / t, a hydroxyl value of 52 KOHmg / g, a melt index of 28 g / 10min, a glass transition temperature of -22.8°C, a melting point of 105.7°C, an initial thermal decomposition temperature of 320°C, an elastic modulus of 525 MPa, a tensile strength of 38.2 MPa, an elongation at break of 185%, a water contact angle of the film of 35°, and a CO 2 The transmittance is 1.78 barrer, O2 The permeability is 3.84 barrer, and the mass loss in phosphate buffer after 35 days of degradation is 95%, and the mass loss in seawater after 35 days of degradation is 67%.
[0079] Comparative Example 3 Dimethyl oxalate and 1,4-butanediol were added into the reactor in molar amounts of 0.30 mol and 0.36 mol, and then titanium oxalate prepared in Comparative Example 1 (accounting for 0.3‰ of the total molar mass of all acid raw materials) and a micro-crosslinking agent pentaerythritol (accounting for 1% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 140° C. within 30 minutes for esterification, the mechanical stirring speed was 140 r, and the polyester oligomer was obtained after the reaction for 3 hours.
[0080] Under nitrogen protection and continuous stirring, add polycondensation catalyst tetrabutyl germanate (accounting for 1.2‰ of the total molar mass of all acid raw materials), stabilizer triphenyl phosphite (accounting for 1.5‰ of the total molar mass of all acid raw materials) and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol (accounting for 0.5‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 195°C, gradually reduce the vacuum degree to 200Pa, react for 90min; continue to reduce the vacuum degree to 50Pa, react for 60min; continue to reduce the vacuum degree to below 10Pa, react for 60min. Discharge the material under nitrogen protection to obtain the target polybutylene oxalate.
[0081] The polybutylene oxalate prepared in this comparative example has an intrinsic viscosity of 0.74 dL / g, a weight average molecular weight of 78000 g / mol, an acid value of 35 mol / t, a hydroxyl value of 54 KOHmg / g, a melt index of 38 g / 10min, a glass transition temperature of -23.6°C, a melting point of 106.8°C, an initial thermal decomposition temperature of 292°C, an elastic modulus of 482 MPa, a tensile strength of 22 MPa, an elongation at break of 167%, a water contact angle of the film of 35°, and a CO 2 The transmittance is 2.35 barrer, O 2 The permeability is 3.87 barrer, and the mass loss in phosphate buffer after 35 days of degradation is 94%, and the mass loss in seawater after 35 days of degradation is 69%.
[0082] Comparative Example 4 Dimethyl oxalate and 1,4-butanediol were added into the reactor in molar amounts of 0.30 mol and 0.36 mol, and the temperature was raised to 140° C. within 30 min for esterification under nitrogen protection. The mechanical stirring speed was 140 r, and the polyester oligomer was obtained after the reaction for 6 h.
[0083] Under nitrogen protection and continuous stirring, add polycondensation catalyst tetrabutyl germanate (accounting for 1.2‰ of the total molar mass of all acid raw materials), stabilizer triphenyl phosphite (accounting for 1.5‰ of the total molar mass of all acid raw materials) and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol (accounting for 0.5‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 195°C, gradually reduce the vacuum degree to 200Pa, react for 120min; continue to reduce the vacuum degree to 50Pa, react for 120min; continue to reduce the vacuum degree to below 10Pa, react for 240min. Discharge the material under nitrogen protection to obtain the target polybutylene oxalate.
[0084] The polybutylene oxalate prepared in this comparative example has an intrinsic viscosity of 0.54 dL / g, a weight average molecular weight of 52000 g / mol, an acid value of 32 mol / t, a hydroxyl value of 44 KOHmg / g, a melt index of 75 g / 10 min, a glass transition temperature of -21.2°C, a melting point of 105.8°C, an initial thermal decomposition temperature of 280°C, an elastic modulus of 454 MPa, a tensile strength of 55.4 MPa, an elongation at break of 342%, a water contact angle of the film of 35°, and a CO 2 The transmittance is 1.77 barrer, O 2 The permeability is 3.45 barrer, and the mass loss is 87% after degradation in phosphate buffer for 35 days, and the mass loss is 56% after degradation in seawater for 35 days.
[0085] Comparative Example 5 Dimethyl oxalate and 1,4-butanediol were added into the reactor in molar amounts of 0.30 mol and 0.36 mol, and then the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 0.3‰ of the total molar mass of all acid raw materials) and the micro-crosslinking agent pentaerythritol (accounting for 1% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 140°C within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 3 hours to obtain a micro-crosslinked polyester oligomer.
[0086] Under nitrogen protection and continuous stirring, organic base polycondensation catalyst 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (accounting for 1‰ of the total molar mass of all acid raw materials), stabilizer triphenyl phosphite (accounting for 1.5‰ of the total molar mass of all acid raw materials) and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid n-octadecyl ester (accounting for 2‰ of the total molar mass of all acid raw materials) were added, and the temperature was gradually raised to 195°C, and the vacuum degree was gradually reduced to 200Pa, and the reaction was carried out for 90min; the vacuum degree continued to be reduced to 50Pa, and the reaction was carried out for 60min; the vacuum degree continued to be reduced to below 10Pa, and the reaction was carried out for 60min. The target polybutylene oxalate was obtained by discharging the material under nitrogen protection.
[0087] The polybutylene oxalate prepared in this comparative example has an intrinsic viscosity of 0.53 dL / g, a weight average molecular weight of 62000 g / mol, an acid value of 48 mol / t, a hydroxyl value of 64 KOHmg / g, a melt index of 55 g / 10min, a glass transition temperature of -23.2°C, a melting point of 106.3°C, an initial thermal decomposition temperature of 288°C, an elastic modulus of 475 MPa, a tensile strength of 21 MPa, an elongation at break of 179%, a water contact angle of the film of 36°, and a CO 2 The transmittance is 1.96 barrer, O 2 The permeability is 3.28 barrer, and the mass loss is 87% after degradation in phosphate buffer for 35 days, and the mass loss is 58% after degradation in seawater for 35 days.
[0088] Example 3 Dimethyl oxalate and 1,4-butanediol were added into the reactor in molar amounts of 0.30 mol and 0.36 mol, and then the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 1‰ of the total molar mass of all acid raw materials) and the micro-crosslinking agent trimethylolpropane (accounting for 1.5% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 150° C. within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 2.5 hours to obtain a micro-crosslinked polyester oligomer.
[0089] Under nitrogen protection and continuous stirring, add stannous trifluoromethanesulfonate as a polycondensation catalyst (accounting for 1.5‰ of the total molar mass of all acid raw materials), triphenyl phosphate as a stabilizer (accounting for 3‰ of the total molar mass of all acid raw materials) and antioxidant 2,6-di-tert-butyl-4-methylphenol (accounting for 2‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 210°C, gradually reduce the vacuum degree to 200Pa, and react for 60min; continue to reduce the vacuum degree to 50Pa, react for 30min; continue to reduce the vacuum degree to below 10Pa, and react for 60min. The target polybutylene oxalate can be obtained by discharging the material under nitrogen protection.
[0090] The polybutylene oxalate prepared in this example has an intrinsic viscosity of 1.62 dL / g, a weight average molecular weight of 158000 g / mol, an acid value of 17 mol / t, a hydroxyl value of 32 KOHmg / g, a melt index of 7 g / 10 min, a glass transition temperature of -22.9°C, a melting point of 105.4°C, an initial thermal decomposition temperature of 338°C, an elastic modulus of 539 MPa, a tensile strength of 54.8 MPa, an elongation at break of 375%, a water contact angle of the film of 37°, and a CO 2 The transmittance is 1.34 barrer, O 2The permeability is 2.92 barrer, and the mass loss is 84% after 35 days of degradation in phosphate buffer and 49% after 35 days of degradation in seawater.
[0091] Example 4 After adding diethyl oxalate and 1,4-butanediol in molar amounts of 0.30 mol and 0.36 mol into the reactor, the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 1.5‰ of the total molar mass of all acid raw materials) and the micro-crosslinking agent propylene glycol (accounting for 1.5% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 145°C within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 2.5 hours to obtain a micro-crosslinked polyester oligomer.
[0092] Under nitrogen protection and continuous stirring, add polycondensation catalyst titanium isopropoxide (accounting for 1.3‰ of the total molar mass of all acid raw materials), stabilizer diphenyl phosphate (accounting for 2.5‰ of the total molar mass of all acid raw materials) and antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol) (accounting for 1.5‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 205°C, gradually reduce the vacuum degree to 200Pa, react for 60min; continue to reduce the vacuum degree to 50Pa, react for 30min; continue to reduce the vacuum degree to below 10Pa, react for 60min. Discharge the material under nitrogen protection to obtain the target polybutylene oxalate.
[0093] The polybutylene oxalate prepared in this example has an intrinsic viscosity of 1.68 dL / g, a weight average molecular weight of 173000 g / mol, an acid value of 19 mol / t, a hydroxyl value of 35 KOHmg / g, a melt index of 9 g / 10 min, a glass transition temperature of -22.7°C, a melting point of 104.8°C, an initial thermal decomposition temperature of 334°C, an elastic modulus of 528 MPa, a tensile strength of 58.4 MPa, an elongation at break of 390%, a water contact angle of 38°, and a CO 2 The transmittance is 1.33 barrer, O 2 The permeability is 2.85 barrer, and the mass loss is 82% after 35 days of degradation in phosphate buffer and 43% after 35 days of degradation in seawater.
[0094] Example 5 After adding diethyl oxalate and 1,4-butanediol in molar amounts of 0.30 mol and 0.42 mol into the reactor, the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 0.5‰ of the total molar mass of all acid raw materials) and the micro-crosslinking agent 1,2,6-hexanetriol (accounting for 1% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 150° C. within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 2 hours to obtain a micro-crosslinked polyester oligomer.
[0095] Under nitrogen protection and continuous stirring, polycondensation catalyst triethyl antimonate (accounting for 1‰ of the total molar mass of all acid raw materials), stabilizer diphenyl phosphate (accounting for 2.5‰ of the total molar mass of all acid raw materials) and antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol) (accounting for 1‰ of the total molar mass of all acid raw materials) were added, and the temperature was gradually raised to 210°C, and the vacuum degree was gradually reduced to 200Pa, and the reaction was carried out for 60min; the vacuum degree continued to be reduced to 50Pa, and the reaction was carried out for 60min; the vacuum degree continued to be reduced to below 10Pa, and the reaction was carried out for 60min. The target polybutylene oxalate was obtained by discharging the material under nitrogen protection.
[0096] The polybutylene oxalate prepared in this example has an intrinsic viscosity of 1.52 dL / g, a weight average molecular weight of 143000 g / mol, an acid value of 16 mol / t, a hydroxyl value of 32 KOHmg / g, a melt index of 16 g / 10 min, a glass transition temperature of -21.9°C, a melting point of 105.4°C, an initial thermal decomposition temperature of 329°C, an elastic modulus of 529 MPa, a tensile strength of 54.9 MPa, an elongation at break of 357%, a water contact angle of the film of 31°, and a CO 2 The transmittance is 2.31 barrer, O 2 The permeability is 3.85 barrer, and the mass loss is 87% after 35 days of degradation in phosphate buffer and 52% after 35 days of degradation in seawater.
[0097] Example 6 After adding diethyl oxalate and 1,4-butanediol in molar amounts of 0.30 mol and 0.45 mol into the reactor, the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 0.3‰ of the total molar mass of all acid raw materials) and the micro-crosslinking agent pentaerythritol (accounting for 1.5% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 140°C within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 3 hours to obtain a micro-crosslinked polyester oligomer.
[0098] Under nitrogen protection and continuous stirring, add stannous oxalate as a polycondensation catalyst (accounting for 2‰ of the total molar mass of all acid raw materials), triphenyl phosphate as a stabilizer (accounting for 1‰ of the total molar mass of all acid raw materials) and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] (accounting for 1‰ of the total molar mass of all acid raw materials) as an antioxidant, gradually increase the temperature to 195°C, gradually reduce the vacuum degree to 200Pa, and react for 90min; continue to reduce the vacuum degree to 50Pa, react for 60min; continue to reduce the vacuum degree to below 10Pa, and react for 90min. The target polybutylene oxalate can be obtained by discharging the material under nitrogen protection.
[0099] The polybutylene oxalate prepared in this example has an intrinsic viscosity of 1.59 dL / g, a weight average molecular weight of 153000 g / mol, an acid value of 24 mol / t, a hydroxyl value of 38 KOHmg / g, a melt index of 18 g / 10 min, a glass transition temperature of -23°C, a melting point of 104.7°C, an initial thermal decomposition temperature of 339°C, an elastic modulus of 546 MPa, a tensile strength of 55.4 MPa, an elongation at break of 320%, a water contact angle of the film of 39°, and a CO 2 The transmittance is 1.27 barrer, O 2 The permeability is 2.68 barrer, and the mass loss is 92% after 35 days of degradation in phosphate buffer and 52% after 35 days of degradation in seawater.
[0100] Example 7 Dimethyl oxalate and 1,4-butanediol were added into the reactor in molar amounts of 0.30 mol and 0.45 mol, and then the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 1.2‰ of the total molar mass of all acid raw materials) and micro-crosslinking agents propylene glycol and pentaerythritol (accounting for 1.5% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 150° C. within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 3 hours to obtain micro-crosslinked polyester oligomers.
[0101] Under nitrogen protection and continuous stirring, add polycondensation catalyst titanium isopropoxide and methyl triethylgermanate (accounting for 1.5‰ of the total molar mass of all acid raw materials), stabilizer triphenyl phosphite (accounting for 1.5‰ of the total molar mass of all acid raw materials) and antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol) (accounting for 1.5‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 210°C, gradually reduce the vacuum degree to 200Pa, react for 60min; continue to reduce the vacuum degree to 50Pa, react for 30min; continue to reduce the vacuum degree to below 10Pa, react for 60min. Discharge the material under nitrogen protection to obtain the target polybutylene oxalate.
[0102] The polybutylene oxalate prepared in this example has an intrinsic viscosity of 1.49 dL / g, a weight average molecular weight of 152000 g / mol, an acid value of 16 mol / t, a hydroxyl value of 30 KOHmg / g, a melt index of 7 g / 10min, a glass transition temperature of -21.3°C, a melting point of 105.7°C, an initial thermal decomposition temperature of 336°C, an elastic modulus of 517 MPa, a tensile strength of 58.7 MPa, an elongation at break of 385%, a water contact angle of the film of 36°, and a CO 2 The transmittance is 2.38 barrer, O 2 The permeability is 3.55 barrer, and the mass loss is 85% after 35 days of degradation in phosphate buffer and 49% after 35 days of degradation in seawater.
[0103] Example 8 After adding diethyl oxalate and 1,4-butanediol in molar amounts of 0.30 mol and 0.36 mol into the reactor, the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 1‰ of the total molar mass of all acid raw materials) and micro-crosslinking agents trimethylolpropane and propylene glycol (accounting for 3% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 140° C. within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 3 hours to obtain micro-crosslinked polyester oligomers.
[0104] Under nitrogen protection and continuous stirring, add polycondensation catalyst tetrabutyl titanate and antimony trioxide (accounting for 1.5‰ of the total molar mass of all acid raw materials), stabilizer diphenyl phosphate (accounting for 2.5‰ of the total molar mass of all acid raw materials) and antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol) (accounting for 1‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 210°C, gradually reduce the vacuum degree to 200Pa, react for 90min; continue to reduce the vacuum degree to 50Pa, react for 60min; continue to reduce the vacuum degree to below 10Pa, react for 60min. Discharge the material under nitrogen protection to obtain the target polybutylene oxalate.
[0105] The polybutylene oxalate prepared in this example has an intrinsic viscosity of 1.47 dL / g, a weight average molecular weight of 136000 g / mol, an acid value of 24 mol / t, a hydroxyl value of 39 KOHmg / g, a melt index of 18 g / 10min, a glass transition temperature of -22.4°C, a melting point of 104.9°C, an initial thermal decomposition temperature of 315°C, an elastic modulus of 550 MPa, a tensile strength of 54.6 MPa, an elongation at break of 357%, a water contact angle of the film of 35°, and a CO 2 The transmittance is 1.86 barrer, O 2The permeability is 3.57 barrer, and the mass loss is 85% after 35 days of degradation in phosphate buffer and 56% after 35 days of degradation in seawater.
[0106] Example 9 Dimethyl oxalate and 1,4-butanediol were added into the reactor in molar amounts of 0.30 mol and 0.36 mol, and then the intrinsic catalyst titanium oxalate prepared in Example 1 (accounting for 0.2‰ of the total molar mass of all acid raw materials) and the micro-crosslinking agent trimethylolethane (accounting for 1% of the total molar mass of all acid raw materials) were added. Under nitrogen protection, the temperature was raised to 130° C. within 30 minutes to carry out ester exchange reaction, the mechanical stirring speed was 140r, and the reaction was carried out for 3 hours to obtain a micro-crosslinked polyester oligomer.
[0107] Under nitrogen protection and continuous stirring, add polycondensation catalyst tetrabutyl germanate (accounting for 0.5‰ of the total molar mass of all acid raw materials), stabilizer triphenyl phosphite (accounting for 5‰ of the total molar mass of all acid raw materials) and antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol (accounting for 2‰ of the total molar mass of all acid raw materials), gradually increase the temperature to 190°C, gradually reduce the vacuum degree to 200Pa, react for 90min; continue to reduce the vacuum degree to 50Pa, react for 60min; continue to reduce the vacuum degree to below 10Pa, react for 60min. Discharge the material under nitrogen protection to obtain the target polybutylene oxalate.
[0108] The polybutylene oxalate prepared in this example has an intrinsic viscosity of 1.45 dL / g, a weight average molecular weight of 129000 g / mol, an acid value of 23 mol / t, a hydroxyl value of 37 KOHmg / g, a melt index of 16 g / 10min, a glass transition temperature of -21.8°C, a melting point of 103.4°C, an initial thermal decomposition temperature of 320°C, an elastic modulus of 540 MPa, a tensile strength of 55.8 MPa, an elongation at break of 349%, a water contact angle of the film of 37°, and a CO 2 The transmittance is 1.82 barrer, O 2 The permeability is 3.64 barrer, and the mass loss is 83% after 35 days of degradation in phosphate buffer and 52% after 35 days of degradation in seawater.
[0109] Compared with Comparative Example 2, the intrinsic catalyst titanium oxalate of the present invention can significantly improve the esterification efficiency, and the synthesized polybutylene oxalate has a higher molecular weight and excellent mechanical properties and stability; compared with Comparative Example 3, the titanium oxalate prepared by the electrocatalytic method has a more stable hydrolysis resistance and can form higher quality polybutylene oxalate; compared with Comparative Example 4, the addition of a micro-crosslinking agent significantly reduces the melt index, making it compatible with the currently large-scale produced degradable polyester and having a wider processing window; compared with Comparative Example 5, the polybutylene oxalate prepared by the organic base condensation catalyst has a lower molecular weight and a higher acid value, and may be accompanied by thermal degradation reactions during the reaction.
[0110] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification in accordance with the aforementioned embodiments, and also produced low melt index polybutylene oxalate with good crystallization ability, mechanical properties and controllable degradation rate.
[0111] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0112] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An efficient preparation method of low melt index polybutylene oxalate, characterized in that: include: Oxalate and 1,4-butanediol are used as raw materials, a micro-crosslinking agent is added, and low melt index polybutylene oxalate is obtained through ester exchange reaction and polycondensation reaction under the action of intrinsic catalyst titanium oxalate and polycondensation catalyst; The micro-crosslinking agent includes a polyol compound, and the polyol compound includes any one or more combinations of glycerol, pentaerythritol, 1,2,6-hexanetriol, trimethylolpropane, and trimethylolethane.
2. The efficient preparation method according to claim 1, characterized in that: The intrinsic catalyst titanium oxalate and the micro-crosslinking agent are added into the reaction system before the transesterification reaction; And / or, the intrinsic catalyst titanium oxalate is prepared by the following steps: at room temperature under nitrogen protection, using metallic titanium as an anode, placing it in an electrolyte containing oxalic acid and passing a constant current of 20-50 mA for more than 60 minutes to obtain the intrinsic catalyst titanium oxalate.
3. The efficient preparation method according to claim 1, characterized in that: The polycondensation catalyst includes a metal organic compound, and the metal organic compound includes any one or more combinations of antimony catalysts, titanium catalysts, tin catalysts, and germanium catalysts; wherein the antimony catalyst includes any one or more combinations of antimony trioxide, antimony acetate, ethylene glycol antimony, and triethyl antimonate; the titanium catalyst includes any one or more combinations of titanium isopropoxide, tetrabutyl titanate, and tetraethyl titanate; the tin catalyst includes any one or more combinations of stannous chloride, stannous oxalate, dibutyltin oxide, stannous octoate, and stannous trifluoromethanesulfonate; the germanium catalyst includes any one or more combinations of germanium dioxide, germanium chloride, methyl triethylgermanate, tetraethyl germanate, and tetrabutyl germanate.
4. The efficient preparation method according to claim 1, characterized in that: include: Under a protective atmosphere, a first mixed reaction system comprising oxalate, 1,4-butanediol, a micro-crosslinking agent and an intrinsic catalyst titanium oxalate is subjected to an ester exchange reaction to obtain a micro-crosslinked polyester oligomer; Under vacuum conditions, a second mixed reaction system comprising the micro-crosslinked polyester oligomer, a polycondensation catalyst, an antioxidant and a heat stabilizer is subjected to a polycondensation reaction to prepare low melt index polybutylene oxalate.
5. The efficient preparation method according to claim 4, characterized in that: The oxalate includes dimethyl oxalate and / or diethyl oxalate; and / or the molar ratio of the oxalate to 1,4-butanediol is 1:1.2 to 1:1.5; and / or, the amount of the micro-crosslinking agent is 1% to 3% of the mole fraction of the oxalate; and / or, the molar ratio of the micro-crosslinking agent to 1,4-butanediol is 1:40 to 1:150; And / or, the amount of the intrinsic catalyst titanium oxalate used accounts for 0.2‰ to 1.5‰ of the mass fraction of oxalate; And / or, the temperature of the transesterification reaction is 130° C. to 150° C., and the time of the transesterification reaction is 120 min to 180 min; And / or, the efficient preparation method comprises: before the ester exchange reaction, placing oxalate, 1,4-butanediol, intrinsic catalyst titanium oxalate, and micro-crosslinking agent together in a reaction chamber, heating to 130°C~150°C within 30 minutes and continuously stirring mechanically, and the ester exchange reaction time is 120min~180min.
6. The efficient preparation method according to claim 2, characterized in that: The amount of the polycondensation catalyst used accounts for 0.5‰ to 2‰ of the mass fraction of the oxalate; And / or, the antioxidant comprises a phenolic antioxidant, and the phenolic antioxidant comprises at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, n-octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,6-di-tert-butyl-4-methylphenol, and 2,2-methylenebis(4-methyl-6-tert-butylphenol); and / or, the amount of the antioxidant is 1‰ to 2‰ of the molar mass of the oxalate; And / or, the heat stabilizer includes a phosphorus stabilizer, and the phosphorus stabilizer includes at least one of phosphorous acid, diphenyl phosphate, triphenyl phosphate, and triphenyl phosphite; And / or, the amount of the heat stabilizer used accounts for 1‰ to 5‰ of the molar mass of the oxalate.
7. The efficient preparation method according to claim 4, characterized in that: include: Before the polycondensation reaction, a polycondensation catalyst, an antioxidant and a heat stabilizer are added; And / or, the temperature of the polycondensation reaction is 190°C~210°C, the pressure in the early stage of polycondensation is 200~1000Pa, and the time in the early stage of polycondensation is 60min~90min; the pressure in the middle stage of polycondensation is 50~200Pa, and the time in the middle stage of polycondensation is 30min~60min; the pressure in the late stage of polycondensation is below 10Pa, and the time in the late stage of polycondensation is 60min~90min.
8. The low melt index polybutylene oxalate prepared by the efficient preparation method according to any one of claims 1 to 7, wherein the structural formula of the low melt index polybutylene oxalate is as shown in formula (1): ; in, R1 is selected from at least one structural unit of a polyol compound, x, y, and n are all integers, x=1-20, y=1-3, and n=20-100; the polyol compound includes at least any one of propylene glycol, pentaerythritol, 1,2,6-hexanetriol, trimethylolpropane, and trimethylolethane.
9. The low melt index polybutylene oxalate according to claim 8, characterized in that: The low melt index polybutylene oxalate has an intrinsic viscosity of 1.4 dL / g to 1.7 dL / g, a weight average molecular weight of 120000 g / mol to 180000 g / mol, an acid value of 15 mol / t to 25 mol / t, a hydroxyl value of 30 KOHmg to 40 KOHmg / g, a melt index of 5 g / 10min to 20 g / 10min at 190° C., and an initial thermal decomposition temperature of 310° C. to 340° C.; And / or, the glass transition temperature of the low melt index polybutylene oxalate is -23°C~21°C, the melting point is 104°C~106°C, the elastic modulus is 500~550MPa, the tensile strength is 50MPa~60MPa, and the elongation at break is 300%~500%; the water contact angle of the polybutylene oxalate film prepared by hot pressing is 30°~40°, the CO2 permeability is 1barrer~3barrer, and the O2 permeability is 2.5barrer~4barrer; the mass loss after hydrolysis for 35 days is 80%~95%, and the residual mass after degradation in seawater for 35 days is 40~60%.
10. Use of the low melt index polybutylene oxalate according to claim 8 or 9 in the fields of agricultural mulch films, artificial seed coatings, drug sustained-release carriers, human implant components or transient electronic devices.
Citation Information
Patent Citations
Method for preparing poly-oxalate-1,4-butylene
CN102219891A
In-situ preparation method of poly (butylene oxalate)
CN115677988A
Polyoxalate copolymer
CN107108865A
Polyester biodegradable pest luring glue and preparation method thereof
CN113754870A
Polyamide elastomer as well as preparation method and application thereof
CN114249889A